1997
DOI: 10.1074/jbc.272.21.13869
|View full text |Cite
|
Sign up to set email alerts
|

Agonist-induced Desensitization, Internalization, and Phosphorylation of the sst2A Somatostatin Receptor

Abstract: Cellular responsiveness to the inhibitory peptide somatostatin (SRIF) or its clinically used analogs can desensitize with agonist exposure. While desensitization of other seven-transmembrane domain receptors is mediated by receptor phosphorylation and/or internalization, the mechanisms mediating SRIF receptor (sst) desensitization are unknown. Therefore, we investigated the susceptibility of the sst2A receptor isotype to ligandinduced desensitization, internalization, and phosphorylation in GH-R2 cells, a clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
129
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 141 publications
(133 citation statements)
references
References 45 publications
4
129
0
Order By: Relevance
“…The present study demonstrated a decline in CRF 1 binding capacity in neocortex, associated with increased CRF 1 mRNA expression. These findings are consistent with a mechanism of transient receptor elimination due to internalization, which leads to enhanced receptor mRNA transcription as has been shown in several other G-protein-coupled receptor systems (8,29,52). In other systems, this ligandinduced receptor internalization has been proposed to contribute to receptor desensitization via cell surface receptor downregulation (8,29), as well as by regulating transcription of mRNA (52).…”
Section: Discussionsupporting
confidence: 78%
“…The present study demonstrated a decline in CRF 1 binding capacity in neocortex, associated with increased CRF 1 mRNA expression. These findings are consistent with a mechanism of transient receptor elimination due to internalization, which leads to enhanced receptor mRNA transcription as has been shown in several other G-protein-coupled receptor systems (8,29,52). In other systems, this ligandinduced receptor internalization has been proposed to contribute to receptor desensitization via cell surface receptor downregulation (8,29), as well as by regulating transcription of mRNA (52).…”
Section: Discussionsupporting
confidence: 78%
“…Most importantly, the fate of the bound phage may be very di erent from that of the natural ligand. After binding free somatostatin, sst 2 has recently been reported to be desensitized, internalized and phosphorylated (Hipkin et al, 1997). It has also been suggested that in some cell lines ligand binding would protect the receptor from degradation, which would increase its half life (Schonbrunn et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Somatostatin binding is known to be rapidly followed by phosphorylation of sst1, sst2A and sst3 receptors by G protein coupled receptor kinases or GRKs (Elberg et al, 2002;Hipkin et al, 1997;Liu and Schonbrunn, 2001;Roth et al, 1997). The GRK family consists of six serine-threonine kinases that specifically bind to and phosphorylate agonist activated GPCRs (Moore et al, 2007;Reiter and Lefkowitz, 2006).…”
Section: Somatostatin Receptor Signaling and Regulation Involve Multimentioning
confidence: 99%
“…Thus, agonist stimulation of GTPγS binding reflects receptor activation of all receptor-interacting G proteins, including the pertussis toxin sensitive G proteins that couple somatostatin receptors to adenylyl cyclase and the pertussis toxin insensitive G proteins that are at least partially responsible for coupling receptors to phospholipase C. Further, since cyclic AMP measurements were made after 15 min of agonist stimulation whereas phosphoinositide production was determined after 50 min of stimulation, the effect of receptor desensitization will differ in the two assays. We now know that desensitization can occur after few minutes of agonist stimulation for several somatostatin receptor subtypes (Beaumont et al, 1998;Elberg et al, 2002;Engstrom et al, 2006;Hipkin et al, 1997;Holliday et al, 2007;Liu et al, 2000). Thus, desensitization will influence second messenger formation in assays conducted in intact cells and the impact of desensitization on such measurements will vary with the time of incubation.…”
Section: Functionally Selective Agonists At Somatostatin Receptorsmentioning
confidence: 99%